Vitamin D deficiency and associated factors in south Korean childbearing women: a cross-sectional study - Yanghee Pang; Oksoo Kim; Jung-Ah Choi; Heeja Jung; Jui Kim; Haeok Lee; Hyangkyu Lee (BMC, 2021)
Abstract Background Adequate levels of vitamin D are important for women of childbearing age as vitamin D helps maintain the pregnancy and ensures proper maternal and fetal bone metabolism and fetal skeletal development. However, vitamin D deficiency is a health problem prevalent in women of all ages, worldwide. This study aimed to determine the current status of serum vitamin D levels and the risk factors for vitamin D deficiency among South Korean nurses of childbearing age. Methods Serum levels of 25-hydroxyvitamin D (25[OH]D) were measured in 1594 registered nurses aged 20 to 45 years who are participants in an ongoing prospective cohort study of the Korean Nurses' Health Study initiated in 2013. The participants completed surveys about demographic and occupational characteristics and physical and psychological health. We examined associations with vitamin D deficiency through multivariable logistic regression analysis. Results The average blood 25(OH) D concentration of the participants was 12.92 ng/mL (4.0-63.4 ng/mL), while the prevalence of vitamin D deficiency (< 20 ng/mL) was 89% (1419/1594). Multivariable logistic regression showed that significant risk factors for vitamin D deficiency included month of sampling (there was a lower level of vitamin D deficiency in winter than in spring, summer, or fall), age (women in their 20s had a lower vitamin D level than those in their 30s and 40s), and stress symptoms. Vitamin D levels were not associated with body mass index, physical activity, and depressive symptoms. Conclusions This study showed a high prevalence of vitamin D deficiency in Korean female nurses. Serum levels of vitamin D were associated with age and season. Vitamin D deficiency should be recognized as one of the primary health concerns among young women. More proactive actions, such as vitamin D supplements and food fortification, are needed to improve vitamin D deficiency in high-risk groups.